2012
DOI: 10.1016/j.juro.2012.05.015
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Transurethral Bladder Biopsy after Intravesical Bacillus Calmette-Guérin Instillation Therapy for Nonmuscle Invasive Bladder Cancer: A Retrospective, Single Center Study and Cumulative Analysis of the Literature

Abstract: Routine transurethral bladder biopsies after a bacillus Calmette-Guérin induction course are not necessary. An individually approach is recommended, tailored from cystoscopic findings and cytology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…While May et al found that bladder biopsies had a positive impact on therapeutic decisions of all NMIBC patients, Highshaw et al found that bladder biopsies are unnecessary in case of negative findings on cystoscopy [17,19]. Similarly, biopsies were found to be unwarranted when cytology and flexible cystoscopy are combined for surveillance [20,21]. To the authors' knowledge, this study is the first to assess the time to recurrence when comparing bladder biopsies to flexible cystoscopy.…”
Section: Discussionmentioning
confidence: 84%
“…While May et al found that bladder biopsies had a positive impact on therapeutic decisions of all NMIBC patients, Highshaw et al found that bladder biopsies are unnecessary in case of negative findings on cystoscopy [17,19]. Similarly, biopsies were found to be unwarranted when cytology and flexible cystoscopy are combined for surveillance [20,21]. To the authors' knowledge, this study is the first to assess the time to recurrence when comparing bladder biopsies to flexible cystoscopy.…”
Section: Discussionmentioning
confidence: 84%
“…It has been established that erythematous lesions are benign in nature in the presence of negative cytology at the time of 3–6 months from the first instillation of BCG. A retrospective study and cumulative analysis by Swietek et al estimated the predictive value of individual lesion type in cystoscopy performed after an induction course of BCG. The authors found that the PPV of erythema with positive cytology was 56% and 9% with negative cytology present.…”
Section: Discussionmentioning
confidence: 99%
“…Given the controversy regarding the diagnostic significance of urine cytology, the management of erythematous lesions of BCG‐treated bladder is heterogeneous. During BCG instillations, erythematous lesions probably signify bladder irritation and in the presence of negative cytology biopsy is not needed ; however, occurrence of erythema and other bladder lesions is common during later follow‐up after a BCG regimen. The objectives of the present study were to classify the cystoscopic appearance of BCG‐induced bladder mucosal lesions during post‐BCG surveillance and to correlate cystoscopy findings with urine cytology and subsequent histological assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the guidelines provide a weak recommendation for patients with high-risk disease having cystoscopy and cytology at 3 months after TURBT and a strong recommendation for such patients having BBs in case of positive cytology and/or positive/suspicious cystoscopy. Available literature provides conflicting data, since some studies suggest that cystoscopy and urinary cytology may be sufficient to assess the efficacy of BCG induction course, thus reserving BBs only to cases whereby such exams yield suspicious/positive findings [5,6], while others recommend routine BBs [7][8][9].…”
Section: Introductionmentioning
confidence: 99%